Microstructured surfaces in highly loaded elastohydrodynamic (EHD)‐contacts – manufacturing and tribological performance. Issue 8 (19th August 2013) - Schrader, T.; Weschta, M.; Engel, U.; Tremmel, S.; Merklein, M.; Wartzack, S.
Abstract In low loaded sliding contacts, as journal bearings or piston contacts, defined microstructures on surfaces were identified for friction reduction purposes and are well established in industrial applications. It is stated that microstructures act as lubricant reservoirs and support lubricant film development. Within the scope of these investigations microstructures are specifically adapted for the tribological load collective of cam follower systems as a representative of highly loaded contacts. For those contacts, the effects of microstructures are still subject of investigations. In this paper a method for efficient microstructuring by micro laser ablation is described. The investigations focus on the determination of the geometric and mechanical properties of the microstructures as well as on the tribological behavior of the microstructured surfaces by two tribological tests.